Grado de satisfacción con la simulación y prácticas docentes tradicionales en la adquisición de competencias clínicas para el manejo de inyecciones y vacunas en estudiantes de la titulación de médico de la Universidad Técnica Particular de Loja septiembre 2012-febrero 2013 - Mendieta Cabrera, Luis Fernando. (2014)
The present research takes him out in order to compare the teaching method over the traditional simulation for both teachers and students of the Degree of Doctor in relation to the management of vaccine injections and to determine the degree satisfying these two groups present. The study was descriptive, prospective, comparative, cross-type focus and quantitative design. The sample used was 44 undergraduate students, 44 seventh-cycle and 4 teachers who have taught the kind of shots and vaccinations for both methods. The results show that both the traditional teaching methodology and simulation to leave students satisfied with an average of 3.40 and 3.87 / 5 on Likert scale; while teachers leave the traditional method satisfied with the value of 3.30 / 5, but the simulation method has an average of 4.5 equivalent to very satisfied. In conclusion, the satisfaction is higher in teaching than students in relation to teaching by simulation.